THE ANALYSIS OF ENVIRONMENTAL ATTITUDES, FUNCTIONAL VALUE AND PRICE TOWARD GREEN PURCHASING INTENTIONS HANDICRAFT PRODUCT IN MANADO - Wowiling, Yishak Gheraldy Gracia (FEB Universitas Sam Ratulangi Manado, 2014)
Green Purchase Intention is conceptualized as the probability and willingness of a person to give preference to products having eco-friendly features over other products in their purchase considerations. Green Purchase Intention is a significant predictor of green purchase behavior, which means that purchase intention is positively affecting the probability of a customer decision that he will buy green products. This research is designed to analyze the influence of Environmental Attitudes, Functional Value and Price toward Green Purchasing Intentions in Manado. The method used to analyze the data is the Multiple Regression Analysis which enables the researcher to analyze the influence of the independent variables to the dependent variable, which is a Green Purchasing Intention. The independent variables in this research are Environmental Attitudes, Functional Value and Price. While the sample of respondents size are 100 respondents who have ever buy green product handicraft. The result of this research shows that there is significant simultaneous and partial influence of Environmental Attitudes, Functional Value and Price on Green Purchasing Intentions in Manado. Therefore, to enhance the Green Purchasing Intentions in Manado these three proponents should be considered intensively. Keywords: environmental attitudes, green product, purchase intention